2012
DOI: 10.1155/2012/159797
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofStaphylococcus epidermidisBiofilm Formation by Traditional Thai Herbal Recipes Used for Wound Treatment

Abstract: Development of biofilm is a key mechanism involved in Staphylococcus epidermidis virulence during device-associated infections. We aimed to investigate antibiofilm formation and mature biofilm eradication ability of ethanol and water extracts of Thai traditional herbal recipes including THR-SK004, THR-SK010, and THR-SK011 against S. epidermidis. A biofilm forming reference strain, S. epidermidis ATCC 35984 was employed as a model for searching anti-biofilm agents by MTT reduction assay. The results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…These results were similar to observations with biofilmforming strain of P. aeruginosa (Chusri, Sompetch et al 2013). Moreover, previous study has revealed the anti-biofilm potency of YSMP against the biofilm-positive strain, S. epidermidis ATCC 35984 (Chusri, Settharaksa et al 2013).…”
Section: Biofilm Inhibition Potency Of Ysmp and Its Componentssupporting
confidence: 91%
See 1 more Smart Citation
“…These results were similar to observations with biofilmforming strain of P. aeruginosa (Chusri, Sompetch et al 2013). Moreover, previous study has revealed the anti-biofilm potency of YSMP against the biofilm-positive strain, S. epidermidis ATCC 35984 (Chusri, Settharaksa et al 2013).…”
Section: Biofilm Inhibition Potency Of Ysmp and Its Componentssupporting
confidence: 91%
“…An ethanol extract of YSMP had no cytotoxic effect and exhibited good anti-inflammatory and anti-oxidant activities. Its ethanol extract additionally possessed anti-biofilm activity against Staphylococcus epidermidis (Chusri, Settharaksa et al 2013) and Pseudomonas aeruginosa (Chusri, Sompetch et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…TSBGlc containing 0.2% DMSO was employed as a negative control. Non-treated control TSBGlc without the test compounds and ampicillin and the medium with each concentration of the test compounds was used as the blank control (Chusri et al, 2012 ). After incubation for 24 h at 37°C, the impact of the combinations on the growth of test bacteria was evaluated using the microplate (ELISA) reader (Bio-rad, USA) at an optical density of 600 nm.…”
Section: Methodsmentioning
confidence: 99%
“…After 3 h, MTT solution was replaced by adding DMSO (200 μl). Bacterial pathogens with an active electron transport system will easily reduce the tetrazolium salt to a water-insoluble purple formazan product (Chusri et al, 2012 ). The color intensity was determined by an ELISA microplate reader (Bio-rad, USA) at 482 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of biofilm formation for the utilized strain was tested based on the procedure described elsewhere [16]. Moreover, Gly-TA was recovered from S. epidermidis strain 1457 based on Wergeland study [17] with slight modifications.…”
Section: Purification Of Gly-tamentioning
confidence: 99%